The Transformation of the Baduy Tourism Village as a Public Space and Provincial Support Area - Anisatul Khanifah; Pambudi Handoyo (Faculty of Social Science, Universitas Negeri Semarang, 2023)
The Baduy tribe is a tribe that still adheres closely to the rules of their ancestors, they live in the village of Kanekes, Lebak Regency which has been designated as a tourist village since 1990 by the Lebak Government. Every year, tourists visiting is increasing. because of this, negative impacts are also increasingly visible, one of which is the violation of Baduy pikukuh (rules). The method used in this study is descriptive qualitative with literature studies which are analyzed using Mac Iver's Concept of Social Change. This research was conducted to determine the impact of the existence of a Baduy tourism village as a provincial buffer area against the rejection of the population and the surrounding environment. The results of this study indicate that there is a clash between the Baduy people and tourists caused by violations such as littering, the use of chemicals such as soap, and the use of electronic goods by tourists which are used to document the Baduy tribe. The existence of this tourist village has a negative path that has emerged so that changing the term to become Saba Baduy Culture is considered a suitable term to represent the Baduy tribe because the meaning of Baduy cultural saba leads to visits to Baduy culture meaning that there are those who